The mixed methods reader - Plano Clark, Vicki L.; Creswell, John w. (Sage Publications, Inc, 2008)
This book provides a collection of key methodological writings in mixed methods research along with a collection of exemplar studies. This cross-disciplinary volume helps define the "literature" of mixed methods research. Selections are draw from the international literature that has appeared across diverse research disciplines over the past 30 years. Key features: writings in the field of mixed methods: methodological selections address research design types and purposes, data collection, data analysis, reporting, and future directions; offers exemplar research studies: examples include published studies from diverse disciplines, including sociology, education, evaluation, health sciences, nursing, and family science; Provides visual diagrams to illustrate exemplar research studies: these diagrams help readers understand how the method's components are implemented and how they can develop diagrams for their own studies